1999
DOI: 10.1111/j.1745-4522.1999.tb00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Oxidation of Commercial Extra Virgin Olive Oil Stored Under Fluorescent Light

Abstract: Extra virgin olive oil is considered to be a high quality oil for health and nutrition and is widely consumed by the Mediterranean population. Presence of natural photosensitizers in olive oil may compromise its nutritional quality if stored in clear plastic or glass container under fluorescent light. In this study, the oxidative stability of commercial extra virgin olive oil (EVOO) and its chlorophyll and tocopherol stripped counterpart (SEVOO) stored at 60C in the dark and under fluorescent light (2650 lux) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…In the glass and plastic bottles, the action of light on the olive oil is favouring photo-oxidation, although in both containers, the pigments of the olive oil (chlorophylls and pheophytins) have an oxidising eVect (Interesse et al, 1971;Khan & Shadidi, 1999;Procida & Cichelli, 1999). In addition, the permeability to oxygen is an inXuence in the plastic bottle, for which reason, at 6 months, the olive oil shows a higher degree of oxidation and an increase in the peroxide index is produced in all the samples.…”
Section: Resultsmentioning
confidence: 97%
“…In the glass and plastic bottles, the action of light on the olive oil is favouring photo-oxidation, although in both containers, the pigments of the olive oil (chlorophylls and pheophytins) have an oxidising eVect (Interesse et al, 1971;Khan & Shadidi, 1999;Procida & Cichelli, 1999). In addition, the permeability to oxygen is an inXuence in the plastic bottle, for which reason, at 6 months, the olive oil shows a higher degree of oxidation and an increase in the peroxide index is produced in all the samples.…”
Section: Resultsmentioning
confidence: 97%
“…Nevertheless, the authors did ind a slight antioxidant efect when the same VOO system was maintained in dark conditions, with a more pronounced efect for chlorophyll a than for chlorophyll b. Other later studies carried out with VOOs have found a positive inluence of the chlorophyllic pigments on the photo-oxidation of oils subjected to diferent conditions of light and storage times [90,97,98]. In relation to this result, Psomiadou and Tsimidou [90] suggested a concentration-dependent photosensitizing activity for pheophytin a that is favored by the availability of oxygen.…”
Section: Thermal Degradation Kineticsmentioning
confidence: 94%
“…chlorophyll), which react with triplet oxygen to form the excited state singlet oxygen. Thus, protection from direct light is required for commercial edible oils (Bradley and Min 1992;Khan and Shahidi 1999).…”
Section: Introductionmentioning
confidence: 99%